On the Relationship of Biogenic Primary and Secondary Organic Aerosol Tracer Compounds on the Aethalometer Model Parameters - Johan Martinsson; Moa K. Sporre; Guillaume Pédehontaa-Hiaa; Hafiz Abdul Azeem (Aerosol and Air Quality Research)
Abstract The aethalometer model has shown to offer a fast, inexpensive and robust method for source apportionment. The method relies on aerosol light absorption attribution, mass balance of the total carbon and results in a fraction of unaccounted, residual carbon that has been associated to biogenic carbon due to its presumably non-light absorbing properties. This residual carbon and its relation to tracers of biogenic primary and secondary organic aerosol was investigated at a rural measurement station in Sweden. Special focus is devoted to 3-methyl-1,2,3-butanetricarboxylic acid (MBTCA), a second-generation oxidation compound in biogenic secondary organic aerosols. The results show that the residual carbon and the biogenic tracers show a high degree of correlation and that the tracers were highly seasonally dependent with largest carbon contributions during summer. MBTCA showed positive correlation with the aethalometer model derived absorption coefficients from fossil fuel carbonaceous aerosol, stressing the suspicion that biogenic aerosol might be falsely apportioned to fossil fuel carbon in the aethalometer model. MBTCA showed an increasing degree of correlation with higher aethalometer absorption coefficient wavelengths. However, spectrophotometric analysis revealed that the ambient concentrations of MBTCA are most likely to low to give a significant response in the aethalometer. These results support the application of MBTCA as a molecular tracer for biogenic secondary organic aerosol and indicates that a large fraction of the aethalometer model residual carbon is of biogenic origin. Future studies should investigate the light absorbing properties of precursor monoterpenes such as α-pinene, their oxidation products and eventual influence on the aethalometer model.